Acute Kidney Injury in a Case Series of Patients with Confirmed COVID-19 (Coronavirus Disease 2019): Role of Angiotensin-Converting Enzyme 2 and Renin-Angiotensin System Blockade - Avantika Chenna; Venu Madhav Konala; Subhasish Bose; Sasmit Roy; Bhaskar Reddy Madhira; Vijay Gayam; Srikanth Naramala; Sreedhar Adapa (Case Reports in Nephrology)
The renin-angiotensin system plays a very critical role in hypertension, diabetes, and kidney and heart diseases. The blockade of the renin-angiotensin system results in the prevention of progression of renal and cardiac damage. There have been controversial hypotheses raised regarding the safety of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers in COVID-19 (coronavirus disease 2019). We present the case series of four patients (2 men and 2 women; 1 Caucasian and 3 African Americans; two survived and two died) with confirmed COVID-19, presenting with respiratory symptoms and acute kidney injury, who have been on angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. Membrane-bound angiotensin-converting enzyme 2 (ACE2) has been implicated as the gateway for viral entry into the human cell in causing the infection. The factors contributing to acute kidney injury are diuretics, iodinated contrast administration, hemodynamic instability apart from ACE inhibitors, and angiotensin receptor blockers. The ACE inhibitors and ARBs were stopped in these patients due to acute kidney injury. We also discussed the role of ACE2 and the renin-angiotensin system (RAS) blockade in patients with COVID-19 infection along with pathogenesis.